Influence of didactic strategies in the learning of biochemistry in students of a university in the Mexican Southeast - Leticia, Zarza-Garcia Addy; Patricia, Kent-Sulu Martha; Esteban, Torres-Zapata Angel; Jesus, Brito-Cruz Teresa del; Eduardo, Moguel-Ceballos Juan (International Journal of Innovative Research and Scientific Studies, 2024)
The purpose of this study was to evaluate the relationship between the teaching strategies used by teachers in teaching biochemistry and the level of learning achieved by students. The teaching-learning process in higher education institutions must adapt to the current demands and requirements of a constantly changing society. University students who study biochemistry need to develop skills that encourage self-learning. The research was carried out with 115 students from a university in the southeast of Mexico, (USoM), to observe and describe a phenomenon. Since there was no control or manipulation of variables, we classify this study as descriptive and "ex post facto," given that the phenomenon had already occurred. Students primarily developed their competencies in comprehension (37%) and analysis (33%). However, when applying for a pilot exam, the majority of responses focused on the aspects of knowledge (36%) and understanding (32%). The present study was carried out under the ethical conditions of informed consent of the participants, promulgated in the Declaration of Helsinki. The participation was voluntary, it was developed with an attitude of empathy, and respect, emotional support, and understanding. The confidentiality and privacy of participants were protected at all times. According to the results observed, a transformation in the didactic strategies employed in the teaching of Biochemistry in the Health Science courses in Mexican universities is suggested.